Integration of soft skills into the program of maritime English - V. Kudriavtseva; S. Barsuk; O. Frolova (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The shipping industry is regulated by international laws with the stakeholders significantly influencing the standards of international transport systems and, therefore, demands highly qualified specialists. The introduction of digital technologies, automatization of working processes, and globalization of international maritime trade create new challenges and increase the requirements for the mariners’ professional competences, thus impacting the training of future specialists.